Cultural stratification on the internet: Five clusters of values and beliefs among users in Britain - Dutton, W; Blank, G (Emerald Group Publishing, 2015)
Purpose: This paper identifies patterns of online stratification based on cultural values and beliefs among internet users in Britain. Methodology/approach: Using a nationally representative random sample of respondents from the 2013 Oxford Internet Survey, we identify groups of individuals who share beliefs about the internet. Findings: Each group represents a distinctive cultural perspective on the internet: e-mersives are fully at home in and positive about the digital environment; techno-pragmatists use the internet for instrumental and work-related purposes; the cyber-savvy use all aspects of the internet, but are also primed to be aware of online risks; cyber-moderates are blase´, neither strongly positive nor negative about the internet; and adigitals harbor overwhelmingly negative beliefs and attitudes about the internet. These cultures are largely unrelated to socio-demographic factors, but appear to be shaped by experience online and general dispositions toward learning, and have major implications for patterns of internet use. Social implications: These cultures of the internet are significant because they suggest that stratification online is strongly influenced by cultural values and meaning because they influence social mobility, skill development, and digital choice.